# Evaluating the infinite product $\prod_{k=2}^{\infty }\left ( 1-\frac{1}{k^2} \right ).$ [closed]

Evaluate

$$\lim_{ n\rightarrow\infty }\prod_{k=2}^{n}\left ( 1-\frac{1}{k^2} \right ).$$

I can't see anything in this limit , so help me please.

-

## closed as off-topic by Najib Idrissi, RecklessReckoner, Mark Fantini, N. F. Taussig, ASBApr 5 '15 at 2:55

This question appears to be off-topic. The users who voted to close gave this specific reason:

• "This question is missing context or other details: Please improve the question by providing additional context, which ideally includes your thoughts on the problem and any attempts you have made to solve it. This information helps others identify where you have difficulties and helps them write answers appropriate to your experience level." – Najib Idrissi, RecklessReckoner, Mark Fantini, N. F. Taussig, ASB
If this question can be reworded to fit the rules in the help center, please edit the question.

Note that $$1-\frac1{k^2}=\left(1-\frac1k\right)\left(1+\frac1k\right)=\frac{k-1}{k}\frac{k+1}{k}=\frac{a_k}{a_{k-1}}$$ with $a_k= \frac{k+1}k$, hence this is a telescoping product, i.e. $$\prod_{k=2}^n\left(1-\frac1{k^2}\right)=\frac{a_2}{a_1}\frac{a_3}{a_2}\cdots\frac{a_n}{a_{n-1}}=\frac{a_n}{a_1}=\frac{n+1}{2n}.$$

-
I think that is \frac{a_n}{a_1} – Sherloek holmes Dec 26 '12 at 19:24

$$\left(1-\frac1{(k-1)^2}\right)\left(1-\frac1{(k)^2}\right)\left(1-\frac1{(k+1)^2}\right)$$

$$=\frac{k(k-2)(k-1)(k+1)k(k+2)}{(k-1)^2k^2(k+1)^2}=\frac{(k-2)(k+2)}{(k-1)(k+1)}$$

Observe that $\left(1-\frac1{(k)^2}\right)$ is cancelled out by the previous & the next term except for the extreme terms, the 1st & the last term leaving behind the 1st part of the 1st term $=\frac{2-1}{2}$ and the 2nd part of the last term $=\frac{n+1}n$

-

Hint: The "typical" term is $\dfrac{k-1}{k}\dfrac{k+1}{k}$. Express the first few terms in this way, and observe the nice cancellations.

For example, here is the product of the first seven terms: $$\frac{1}{2}\frac{3}{2}\frac{2}{3}\frac{4}{3}\frac{3}{4}\frac{5}{4}\frac{4}{5}\frac{6}{5}\frac{5}{6}\frac{7}{6}\frac{6}{7}\frac{8}{7}\frac{7}{8}\frac{9}{8}=\frac{9}{2\cdot 8}.$$

-

Let $g(k)=\frac{k-1}{k}$. Then this product is:

$$\prod_{k=2}^n \frac{g(k)}{g(k+1)}$$

which is a telescoping product, and thus equal to $\frac{g(2)}{g(n+1)}$

-

$$1-\frac{1}{k^2} = \frac{(k-1)(k+1)}{k^2}$$ $$\prod_{k=2}^{n}\left ( 1-\frac{1}{k^2} \right ) = \underbrace{\frac{2-1}{2}}_{\text{from first}} \times \underbrace{\frac{(n+1)}{n}}_{\text{from last}}$$

-